Computational insights into octyl-D-xyloside isomers towards understanding the liquid crystalline structure: physico-chemical features - Bayach, I.; Manickam Achari, V.; Wan Iskandar, W.F.N.; Sugimura, A.; Hashim, Rauzah (Taylor & Francis, 2016)
ABSTRACT: We applied density functional theory to study octyl-D-xyloside isomers in order to explain the features responsible for the liquid crystal mesophases. Compared to a glucoside, the xylose headgroup has a proton instead of the hydroxymethyl group on C5. Thus, a xyloside has a reduced headgroup volume that renders it less hydrophilic. Our results have shown that the xylose headgroup may adopt stable pyranose and furanose conformations, which may lead to different effective headgroup hydrophilicities. These features are probably responsible for forming two non-equivalent inverse micelles, which are self-assembled into a cubic discontinuous phase with a space group of Fd3m commonly found for xylosides. While different factors are responsible for controlling the relative stability of each isomer, the role of intramolecular hydrogen bonding was highlighted for the investigated single molecule. The polarisable continuum model was used to take into account the solvent effect in order to understand the molecular behaviour in very polar systems. Results from calculations carried out in gas phase were used for comparative purposes. The molecular electrostatic potential calculations for these xylolipids demonstrate sugar amphoterism, which is implicated in the heterogeneity nature of lipid self-assembly.